The mercapturomic profile of health and non-communicable diseases - Gonçalves-Dias, Clara (2019)
iNOVA4Health–UID/Multi/04462/2013, a program financially supported by Fundação para a Ciência e Tecnologia/Ministério da Educação e Ciência, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement is acknowledged (Ref: 201601-02-021). Authors supported by Fundação para a Ciência e a Tecnologia (FCT–Portugal): for V.S.; PD/BD/105892/2014 for C.G.-D.;RNEM-LISBOA-01-0145-FEDER-022125022125 for J.M.; SFRH/BD/130911/2017 for M.J.C.; D/BD/114257/2016 for N.R.C.; Programa Operacional Potencial Humano and the European Social Fund (IF/01091/2013) for A.M.M.A.